2021
DOI: 10.1007/s00204-021-03162-5
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase poisoning by the flavonoid nevadensin triggers DNA damage and apoptosis in human colon carcinoma HT29 cells

Abstract: Nevadensin, an abundant polyphenol of basil, is reported to reduce alkenylbenzene DNA adduct formation. Furthermore, it has a wide spectrum of further pharmacological properties. The presented study focuses the impact of nevadensin on topoisomerases (TOPO) in vitro. Considering the DNA-intercalating properties of flavonoids, first, minor groove binding properties (IC50 = 31.63 µM), as well as DNA intercalation (IC50 = 296.91 µM) of nevadensin, was found. To determine potential in vitro effects on TOPO I and TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Unexpectedly, administration of A. nilotica at doses of > 200 mg/kg potentiated the DNA- damaging effect induced by the direct-action alkylating agent MNU in MN and comet assays. These findings can be explained by the fact that many flavonoids intercalate into DNA and inhibit DNA topoisomerases (I and II) by exerting their mutagenic effects [ 44 , 45 ]. This observation directly agreed with previous literature, which showed that some antioxidant compounds with biphasic nature might exert mutagenic and antimutagenic effects depending on the mutagenic agent and test system used [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, administration of A. nilotica at doses of > 200 mg/kg potentiated the DNA- damaging effect induced by the direct-action alkylating agent MNU in MN and comet assays. These findings can be explained by the fact that many flavonoids intercalate into DNA and inhibit DNA topoisomerases (I and II) by exerting their mutagenic effects [ 44 , 45 ]. This observation directly agreed with previous literature, which showed that some antioxidant compounds with biphasic nature might exert mutagenic and antimutagenic effects depending on the mutagenic agent and test system used [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2017 )), HT-29 (colon carcinoma cells (Müller et al. 2021 )) and HepG2] to cover analytes with no available reference compounds. The integrated peak areas were further processed using Microsoft Excel 2019 (Microsoft Corporation, Redmond, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It exhibits many in vitro pharmacological and biological activities such as anti-inflammatory, anti-microbial, and anti-tuberculosis [ 10 , 11 ]. In addition, studies have shown that nevadensin induced the intrinsic apoptosis pathway by interrupting the cell cycle and activating caspase-3 and caspase-9, leading to DNA damage and apoptosis in human colon cancer HT29 cells [ 12 ]. It was also associated with caspase-3-mediated mitochondrial apoptosis in many HCC cells, such as BEL-7404, HepG2, and SMMC-7721 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%